Difficulties of employing e-learning at the university from the students' point of view - Salih Ali, Lect. Asmaa (Basra studies journal, 2023)
The aim of the current research is to identify the difficulties of employing e-learning from the students’ point of view. The research sample were male and female students of the College of Education for Human Science, University of Basra, in the second and third levels from departments (educational and psychological sciences، psychological guidance، educational guidance، Arabic language، history and geography). They were (216) male and female students، and after applying the E-Learning Difficulties Scale (Al-Awada، 2012)، the research results showed the following: 1- The members of the research sample suffer from difficulties in employing e-learning in their university studies. 2- There are no statistically significant differences due to the variables (gender، school stage) in the difficulties of employing e-learning in the study.